Measuring Spiritual Needs in a Secular Society: Validation and Clinimetric Properties of the Danish 20-Item Spiritual Needs Questionnaire - Stripp, Tobias Kvist (Journal of religion and health, 2022)
In secular cultures, such as Denmark, tools to measure spiritual needs are warranted to guide existential and spiritual care. We examined the clinimetric properties of the Danish version of the Spiritual Needs Questionnaire (DA-SpNQ-20) based on a digital survey in a test-retest setup. A convenience sample was reached via social media and student platforms. A total of 325 (148 for retest) respondents were included in the analysis. The sample was randomly split into two groups (A and B) and used for exploratory (EFA) and confirmatory factor analysis (CFA) by structural equation modeling, respectively. SpNQ dimensions had an internal consistency with Cronbach’s alpha between 0.73 and 0.93. The four factors of the SpNQ were supported by both EFA and CFA as follows: religious needs, existential needs, inner peace needs, and generativity needs. The instrument showed good internal consistency, good test-retest reliability, and acceptable structural validity in the sample of relatively young and healthy persons.